Avaliação do suporte à transferência das ações de educação permanente em saúde: perspectiva das equipes de enfermagem da estratégia saúde da família - Oliveira, Kesia Jacqueline Ribeiro (2017)
This study evaluates the support to the transfer of the actions of Permanent Education in Health (PEH), from the perspective of the Nursing professionals of the Family Health Strategy. The objective was to evaluate the support to the transfer of PEH actions from the perspective of the Nursing professionals in the Family Health Strategy. This is a quantitative, exploratory-descriptive, cross-sectional study of Survey type, carried out in the municipalities of Maceió and Arapiraca, comprising 36 Family Health Teams. The sample was made for non-probabilistic convenience, composed of 152 Nursing professionals. Data was collected through two instruments: 1) a questionnaire containing the characterization of the participants and the actions of PEH and 2) by the Scales of Support to the Transfer of Training (SST). For the data analysis, descriptive statistics were used with the help of the Statistical Package for the Social Sciences software, version 21. The results indicated that in relation to the characterization of the participants there was a predominance (91.4%) of the female sex with a mean age of 41, 07 years; in PEH activities: 67.1% were offered by the Municipal Health Department with hours worked in up to 10 hours (65.1%); through lectures (33.6%), which contributed to the performance of the FHU (83.5%); The data obtained by SSTs in the psychosocial support dimension: 36.18% of the professionals indicated low managerial, social and organizational support in the work environment; 40.79% indicated low support of the immediate leadership in the removal of obstacles in the work environment, a situational support factor. And for the consequences associated with the use of the new skills, 31.58% had low access to information, as well as low support from peers or superiors. In the material support category, 84.87% indicated low support for quality, quantity and availability of material and financial resources, as well as for quality and adequacy of the physical environment. Thus, it is necessary to plan PEH strategic actions by the managers, so that they follow the state PEH plan and, thus, can meet the real needs and adequacy of the material support and the environment in which they are inserted.